The histone H4K20 methyltransferase SUV4-20H1/KMT5B is required for multiciliated cell differentiation in Xenopus - Angerilli, Alessandro; Tait, Janet; Berges, Julian; Shcherbakova, Irina; Pokrovsky, Daniil; Schauer, Tamas; Smialowski, Pawel; Hsam, Ohnmar; Mentele, Edith; Nicetto, Dario; Rupp, Ralph AW (Life science alliance, 2023)
H4 lysine 20 dimethylation (H4K20me2) is the most abundant histone modification in vertebrate chromatin. It arises from sequential methylation of unmodified histone H4 proteins by the mono-methylating enzyme PR-SET7/KMT5A, followed by conversion to the dimethylated state by SUV4-20H (KMT5B/C) enzymes. We have blocked the deposition of this mark by depleting Xenopus embryos of SUV4-20H1/H2 methyltransferases. In the larval epidermis, this results in a severe loss of cilia in multiciliated cells (MCC), a key component of mucociliary epithelia. MCC precursor cells are correctly specified, amplify centrioles, but ultimately fail in ciliogenesis because of the perturbation of cytoplasmic processes. Genome-wide transcriptome profiling reveals that SUV4-20H1/H2-depleted ectodermal explants preferentially down-regulate the expression of several hundred ciliogenic genes. Further analysis demonstrated that knockdown of SUV4-20H1 alone is sufficient to generate the MCC phenotype and that its catalytic activity is needed for axoneme formation. Overexpression of the H4K20me1-specific histone demethylase PHF8/KDM7B also rescues the ciliogenic defect in a significant manner. Taken together, this indicates that the conversion of H4K20me1 to H4K20me2 by SUV4-20H1 is critical for the formation of cilia tufts.
Gesehen am 21.06.2023